880-01 Geng xin Zhongguo : wei le yi ge ke chi xue de wei lai = Updating China : projects for a sustainable future = Nachhaltiges Planen und Bauen in China - Li, Xiangning; Dubrau, Christian, 1978- (Berlin : DOM Publishers)
PSZJBL